Tracing Human IgE B Cell Antigen Receptor-Bearing Cells With a Monoclonal Anti-Human IgE Antibody That Specifically Recognizes Non-Receptor-Bound IgE - Zghaebi, Mohammed; Byazrova, Maria; Flicker, Sabine; Villazala-Merino, Sergio; Campion, Nicholas J.; Stanek, Victoria; Tu, Aldine; Breiteneder, Heimo; Filatov, Alexander; Khaitov, Musa; Niederberger-Leppin, Verena; Eckl-Dorna, Julia; et al. (Frontiers in Immunology, 2021)
Up to 30% of the population suffers from immunoglobulin E (IgE)-mediated allergies. Despite current stepwise gating approaches, the unambiguous identification of human IgE producing cells by flow cytometry and immunohistology remains challenging. This is mainly due to the scarcity of these cells and the fact that IgE is not only expressed in a membrane-bound form on the surface of IgE producing cells in form of the B cell antigen receptor (BCR), but is more frequently found on various cell types bound to the low and high affinity receptors, CD23 and FcεRI, respectively. Here we sought to develop a sequential gating strategy for unambiguous detection of cells bearing the IgE BCR on their surface. To that aim we first tested the monoclonal anti-IgE antibody omalizumab for its ability to discriminate between IgE BCR and receptor-bound IgE using cells producing IgE or bearing IgE bound to CD23 as well as basophils exhibiting FcεRI receptor-bound IgE. Using flow cytometry, we demonstrated that omalizumab recognized IgE producing cells with a high sensitivity of up to 1 IgE+ cell in 1000 human peripheral blood mononuclear cells (PBMCs). These results were confirmed by confocal microscopy both in cell suspensions as well as in nasal polyp tissue sections. Finally, we established a consecutive gating strategy allowing the clear identification of class-switched, allergen-specific IgE+ memory B cells and plasmablasts/plasmacells in human PBMCs. Birch pollen specific IgE+ memory B cells represented on average 0.734% of total CD19+ B cells in allergic patients after allergen exposure. Thus, we developed a new protocol for exclusive staining of non-receptor bound allergen-specific IgE+ B cell subsets in human samples.